Talk show Edukasi Skabies: Upaya Promotif di Desa Babakan Madang, Bogor - Wijaya, Meiliyana; Gaverio, Nicholas Francisco; Olivia, Vera; Joprang, Freggy Spicano; Hananta, Linawati (Jurnal SOLMA, 2025)
Background: Scabies, also known as "kudis," is a skin disease commonly found in areas with high population density and poor sanitation, such as rural regions. This study aimed to increase the knowledge and awareness of residents regarding scabies through an educational talk show. The activity was conducted in Babakan Madang Village, Bogor, West Java, an area with a high incidence of scabies. Methods: This community engagement activity was conducted through a two-way interactive educational approach in the form of a talk show, commencing with a pre-test, followed by an expert-led interactive discussion on the identification, prevention, and treatment of scabies, a question-and-answer session, a post-test, and the provision of appropriate scabies medication to residents diagnosed with the condition. Results: The results showed a significant increase in post-test scores compared to pre-test scores, indicating an improvement in residents' knowledge about Sarcoptes scabiei, the causative agent of scabies, including its symptoms and proper treatment. Conclusions: In conclusion, the talk show method proved effective in raising public awareness about scabies and equipping affected residents with appropriate treatment ointments, thereby supporting government efforts to reduce the prevalence of scabies in the region.